Pemanfaatan Media Digital dalam Konseling Kelompok Berbasis Value Clarification untuk Meningkatkan Toleransi Remaja - Fajar Rosyidi; Niken Dwi Saputri (Technocouns: Journal of Technology in Guidance and Counseling, 2025)
This research aimed to explore the effectiveness of group counseling based on value clarification in enhancing tolerance among adolescents, with the integration of digital media as a supporting tool. The study applied a quasi-experimental approach with a one-group pretest-posttest design, involving 9 adolescents aged 15-18 years from Kudus who were identified as having low tolerance levels. The intervention consisted of six group counseling sessions, each lasting 90 minutes, utilizing digital media such as educational videos, online discussion forums, and interactive infographics to stimulate value clarification. Data on tolerance levels were collected using a tolerance scale before and after the intervention. The results indicated a significant improvement in tolerance, with the average posttest score increasing by 18.34 points compared to the pretest. Statistical analysis using paired sample t-test confirmed the effectiveness of the intervention, with a p-value of 0.000. The findings suggest that value clarification in group counseling, supported by digital media, is a promising approach to enhancing tolerance among adolescents. This study contributes to the development of counseling programs aimed at promoting inclusive attitudes and intercultural understanding in educational settings. Further research is needed to explore the long-term effects and practical implementation of digital media integration in counseling.